Study of the energy potential of pelletized Ecuadorian rice husk for use as fuel - Velázquez Áraque, Luis Enrique; Aguilar Sierra, Josué Manuel; Tulcán Álvarez, Edgar Alejandro (Ingeniería Química y Desarrollo, 2022)
Through the present research work will be released a study of the possibilities of pelletization of Ecuadorian rice husk and its use as a biofuel, because Ecuador, its agroindustrial industry this waste is not used in its entirety for which it is proposed to the use as a source of energy of biological origin thus giving rise to a product called pellet, which could be evidenced in previous research the energy potential of the exclusive use of this rice husk biomass, for which, an improvement was proposed to this product by adding a binder such as cassava starch of biological origin in different proportions which are subjected to different analyzes and it was obtained that the best ratio is 70% rice husk and 30% starch giving optimum values ​​for their production.